TIN MINING LICENSING IN THE ERA OF LOCAL GOVERNMENT REFORM - Fendi Haryono (PT Wahana Global Education, 2026)
The dynamics of the legal politics of regulating mineral and coal licensing authorities have undergone significant changes. Initially, the authority was given by law to local governments, and now this authority is taken over by the central government. The purpose of this research is to find out the direction and philosophical basis of the legal politics behind the amendments to the Mineral and Coal Law and its implications for the mining licensing authority. This study aims to identify from research are that some significant changes in mining licensing authority can be identified and the terms and stages. The research method uses normative legal research. The research study results concluded that the centralistic paradigm of granting permits in an integrated manner also marks the shift of regional authority from attribution to delegation authority. Affirming the political direction of mining law is a priority for the central government's authority when several strategic articles have been amended and even eliminated. Amendments to the formulation in Article 4 (mineral and coal control rights) and Article 6 (mining management authority) of the 2020 Mineral and Coal Law show no longer partiality for local governments to allocate mining licensing authority.